Public opinion on systems for feeding back views to the National Health Service. Issue 6 (26th November 2003) - Entwistle, V A; Andrew, J E; Emslie, M J; Walker, K A; Dorrian, C; Angus, V C; Conniff, A O
Abstract : Objectives: To explore public opinions about different systems for feeding back views about health services to the National Health Service. Design: Questionnaire survey. Setting: NHS Grampian, Scotland, UK. Participants: A random sample of 10 000 adults registered with a general practitioner in Grampian was invited to opt in to the study; 2449 were sent questionnaires. Outcome measures: Opinions about different feedback mechanisms and their likely effectiveness in three scenarios; reasons for preferring particular mechanisms. Results: Of 1951 respondents, over 80% thought patient representatives would be a good way for people to pass on their ideas about the NHS and would help to improve it. Patient representatives were the most widely preferred course of action for two out of three scenarios. People explained their preferences for particular feedback systems mainly in terms of their ease of use, the perception that they would be listened to, and the likelihood of anything being done about what they said. However, people varied in their judgements about the likely effectiveness of different feedback systems. Preferences for particular systems varied according to the types of situation considered. Some people are reluctant to approach clinical staff with concerns about healthcare quality. A substantial minority have no confidence that their concerns would be listened to or acted upon, however they were expressed. Conclusion: The "patient representative" function has substantial popular support and could facilitate local learning and action to improve the quality of health services from users' perspectives. Feedback systems must demonstrate their effectiveness if they are to gain and retain public confidence.